Combined immunoprecipitation and agglutination for the detection of the heterodimeric molecule: human chorionic gonadotropin as a study model - Tayapiwatana C. (2014)
Double-particle reversed passive hemagglutination (RPHA) was performed for the detection of an intact heterodimeric form of human chorionic gonadotropin (intact hCG) composed in Profasi hCG (P-hCG). This technique relied on two mixed types of human O RBC, which were individually coated with two distinct monoclonal antibodies that recognized alpha or beta subunit of hCG, i.e. ALC-1 and BEL-5, respectively. The positive hemagglutination result was achieved by this technique. However, in the BEL-5 coated single-particle control system, positive results for both P-hCG and beta subunit hCG solution were realized. The occurrence of beta-multimer hCG was a causative molecule revealed by the hemagglutination inhibition technique. Thereby, the novel method called "combined immunoprecipitation and agglutination" was developed to overcome this problem. The free beta subunit together with the betamultimer hCG were eliminated from other forms presented in P-hCG after using the ALC-1 coated particles. The precipitated particles, which captured the heterodimer hCG molecule, reacted further with soluble BEL-5 to subsequently form a trellis. A positive result was obtained only with P-hCG, but not with beta subunit hCG or hLH. This study is inferable as a model for the detection of heterodimeric molecule by an elementary method.